Transesterification of palm oil for biodiesel productionusing ni / cao supported with alumina beads / Zainal Kifli Abdul Razak ... [et al]. - Abdul Razak, Zainal Kifli; Kamarullah, Shahida Hanum; Mohd Shohaimi, Norshahidatul Akmar; Mohd Kamalluddin, Noor Aini Izatie; Wan Teh, Wan Nurul Syamimi (Universiti Teknologi MARA Cawangan Pahang, 2020)
Biodiesel has gained interest among researchers as an alternative fuel to replace fossil fuels due to its sustainability. Biodiesel can be produced by transesterification of plant oils with methanol using suitable catalysts. Recently, application of heterogeneous catalyst has attracted considerable interest in biodiesel production compared to homogenous catalyst due to their reproducibility. In this study, biodiesel was produced by transesterification of palm oil with methanol catalyzed by calcium oxide coated on alumina beads and doped with nickel. The objective of this study is to determine the optimum catalyst loading of the transesterification process. The catalyst was prepared by heating a mixture of calcium nitrate, nickel(II) nitrate hexahydrate and alumina beads at 700°C. This temperature was selected after performing a thermogravimetric analysis on the calcium nitrate. In this study, the highest yield of 24.24% was obtained from transesterification reaction at optimum conditions of 5 hour reaction time, 1:25 oil-methanol molar ratio and 65°C of reaction temperature with 4 wt% of catalyst loading. Quantification and identification of biodiesel was done using gas chromatography mass spectrometry (GCMS)